(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
We were sythesise ligands based on 3 (2-pyridyl)-1,2,4-triazole and their coordination compounds with palladium (II) in metal to ligand ratios 1:1 and 1:2. In compounds were determined the influence of substituents on coordination behavior of the ligands. Coordination compounds were studied by means of IR- and NMR-spectroscopy.